A split face comparative interventional study to evaluate the efficacy of fractional carbon dioxide laser against combined use of fractional carbon dioxide laser and platelet-rich plasma in the treatment of acne scars - Devi Priya; Shivakumar Patil (Wolters Kluwer Medknow Publications, 2023)
Background: Fractional carbon dioxide laser (FCL) is an established treatment option for acne scars, but use of platelet-rich plasma (PRP) as an adjuvant still requires elaborate studies. Aim: To compare the efficacy and safety of FCL alone and combined use of FCL with PRP in the treatment of acne scars. Materials and Methods: This was a split-face (right-left) comparative study including 32 patients with moderate to severe acne scars. The patients underwent three sessions of FCL along with PRP and FCL alone on right and left sides of the face, respectively, at an interval of 6 weeks. Goodman and Baron qualitative and quantitative scores were used for the evaluation of results along with visual analog scale (VAS) for patient satisfaction and physician assessment of scars. Adverse effects following the procedure were also evaluated and compared. Results: There was significant improvement of scars over both sides of the face, but the difference between right and left sides was not statistically significant according to Goodman and Baron qualitative (p 0.9115) and quantitative score (p 0.6957). On assessing VAS score, patients were more satisfied with the right side, but the values were not statistically significant (p 0.8571). Physician assessment grading showed comparable results over both the sides (p 1). There was no difference in adverse effects between both sides of the face. Conclusions: Inclusion of intradermal PRP to FCL did not produce any statistically significant synergistic effects in the treatment of acne scars.